Effects of combined addition of Ca and Y on the corrosion behaviours of die-cast AZ91D magnesium alloy. (15th April 2020) - Woo, Sang Kyu; Blawert, Carsten; Yasakau, K.A.; Yi, Sangbong; Scharnagl, Nico; Suh, Byeong-Chan; Kim, Young Min; Sun You, Bong; Dong Yim, Chang
Highlights: The combined addition of calcium and yttrium significantly improved the corrosion resistance of the die-cast AZ91D alloys. The formation of the Al-Mn-Y phase instead of the Al-Mn-Fe phase significantly reduced the VPD values, which decreased micro-galvanic corrosion. The stability of the surface film of the AZXW911 alloy were improved by the adding of a small amount of Y. Abstract: The corrosion behaviours of commercial AZ91D alloy and Ca–Y-containing AZ91 alloy, fabricated by casting, were evaluated, and their microstructural changes and surface properties were analysed. The Ca–Y-containing AZ91 alloy showed superior corrosion resistance compared with the AZ91D alloy mainly because of the decrease in the Volta potential difference between the matrix and the secondary phases formed in the Ca–Y-containing alloy, such that micro-galvanic corrosion was significantly suppressed. Furthermore, passivity and stability of the surface film improved with the addition of Y to the AZ91 alloy. Thus, the overall corrosion resistance was significantly improved in the Ca–Y-containing AZ91 alloy.